Women in the Boardroom for Better Governance Management and Financial Performance - Chotiyaputta, Veerisa (Asian Administration and Management Review, 2019)
One of recent topics discussed extensively in boardroom is how to refresh board of directors’ composition to counter with fast-moving business environment. Gender diversity is proved to be one solution to contribute and strengthen boardroom’s effectiveness. Even though empirical evidences produce inconclusive results about the effect of having or increasing women in boardroom would positively impact companies’ financial performance, many countries and business organizations put this issue as top agenda as it can represent the high level of commitment toward good corporate governance practices. Finally, this paper is reflected the future role of women in boardroom by highlighting the important fact and key strength of women’s skills in tech experience which is deemed necessarily to overcome velocity of current and future technological disruption.